The use of kemiri seed meal (Aleurites mollucana Willd.) in native chickens diet - Resnawati, Hesti; Iskandar, S; ., Surayah (Indonesian Journal of Animal and Veterinary Sciences, 1998)
An experiment was carried out to evaluate the optimum level of kemiri seed meal for native chickens. One hundred unsexed day-old native chickens were reared in 20 cages with five birds per cage. Five dietary treatments were formulated to contain different levels of kemiri seed meal: 0% (R0), 5% (R5), 10% (R10), 15% (R15) and 20% (R20). All diets were formulated to be isoprotein and isoenergy with 14% crude protein and 2,850 kcal ME/ kg diet. The experiment was arrangedin a completely randomized design with five treatments and four replicates. Feed consumption, body weight gain and intestinal weight were significantly (P<0.01) affected by inclusion of kemiri seed meal in the diet. But the feed conversion, carcass weight and liver weight were not affected significantly. It was concluded that kemiri seed meal can be added until 5% in the diet of growing native chickens. Â  Key words : Native chickens, kemiri seed meal, growth